From tetraploid to diploid, a pangenomic approach to identify genes lost during synthetic diploidization of Eragrostis curvula - Carballo, Jose; Bellido, Andrés Martin; Selva, Juan Pablo; Zappacosta, Diego; Gallo, Cristian Andres; Albertini, Emidio; Caccamo, Mario; Echenique, Viviana (Frontiers in Plant Science, 2023)
In Eragrostis curvula, commonly known as weeping lovegrass, a synthetic diploidization event of the facultative apomictic tetraploid Tanganyika INTA cv. originated the sexual diploid Victoria cv. Apomixis is an asexual reproduction by seeds in which the progeny is genetically identical to the maternal plant. To assess the genomic changes related to ploidy and to the reproductive mode occurred during diploidization, a mapping approach was followed to obtain the first E. curvula pangenome assembly. In this way, gDNA of Tanganyika INTA was extracted and sequenced in 2x250 Illumina pair end reads and mapped against the Victoria genome assembly. The un-mapped reads were used to do the variant calling while the mapped reads were assembled using Masurca software. The length of the assembly was 28,982,419 bp distributed in 18,032 contigs and the variable genes annotated in these contigs rendered 3,952 gene models. Functional annotation of the genes showed that the reproductive pathway was differentially enriched. PCR amplification in gDNA and cDNA of Tanganyika INTA and Victoria was conducted to validate the presence/absence variation of five genes related to reproduction and ploidy. The polyploid nature of the Tanganyika INTA genome was also evaluated through the variant calling analysis showing the SNP coverage and allele frequency distribution a segmental allotetraploid pairing behavior. The results presented here suggest that the genes lost in Tanganyika INTA during the diploidization process conducted to the suppression of the apomictic pathway, affecting severely the fertility of Victoria cv.